APLIKASI MODIFIED PROCTOR PADA ROLLER COMPACTED NO-FINES CONCRETE DENGAN AGREGAT 5-10 mm - ABDIAS TANDY ARRANG (Publikasi dan UKI Press UKI Toraja., 2016)
The usage of no-fines concrete as pavement currently was being utilized. It was constituted by diversity effort of concrete cement pavement construction material, besides no-fines concrete pavement having benefit that reduce water pond on pavement surface rapidly because of its pervious. Permeability character of no-fines concrete will recharge groundwater deposit therefore more environmental friendly. Problem faced is low strength of no-fines concrete as compared to conventional concrete. Therefore it is required the effort of increasing the strength of no-fines concrete by increase concrete density that is done by roller machine. No-fines concrete that is compacted by roller machine is called Roller Compacted No-fines Concrete (RCNC). This research analyzed the increase of concrete properties especially compression strength and split tensile strength effected by external compaction using modified proctor in creating the laboratory specimen. Materials of no-fines concrete utilized Clereng coarse aggregate with size 5-10 mm, Gresik Portland cement and the aggregate cement ratio is 4 and 6. To accelerating the hardening concrete utilized admixture type C which is sikaset accelerator with 20% of total water volume. The blow variation of modified Proctor per layer is 28, 42 and 56. Compression test and split tensile test been done at the age of 1 and 28 days. Result of research showed the increase of concrete specific gravity and compression strength in line with the increase of blow variation. RCNC specific gravity acquired ranging between 1,544 and 1,788. Compression strength at the age of 28 days acquired were (1) aggregate cement ratio 4 with 28, 42, 56 blows per layer were 21,47 MPa, 22,92 MPa, 26,55 MPa (2) aggregate cement ratio 6 each were 8,48 MPa, 10,51 MPa, 14,82 MPa. Split tensile strength at the age of 28 days were (1) aggregate cement ratio 4 with 28, 42, 56 blows per layer each were 2,27 MPa, 2,92 MPa, 3,13 MPa (2) aggregate cement ratio 6 each were 1,63 MPa, 1,83 MPa, 2,08 MPa.